The INCREASING THE PROFESSIONALISM OF ELEMENTARY SCHOOL TEACHERS THROUGH WRITING SCIENTIFIC PAPERS, PTK AND NUMERIC LITERACY - Gularso, Dhiniaty Gularso; Warniasih, Kristina (Jurnal Berdaya Mandiri, 2024)
Lack of access to information about writing scientific papers, classroom action research and numeric literacy. This causes a lack of professional teachers who produce scientific papers, classroom action research and numeric literacy. PGRI Yogyakarta University is one of the universities that has a professional education program department, there are still several professional teachers who have not written scientific work. classroom action research and numeric literacy. Even though there are already professional teachers who have carried out the writing of works. There are still many teachers who are too busy teaching and preparing material every day which means teachers no longer have time to write work. Based on these problems, the method used is an academic seminar to increase teacher professionalism through scientific work, classroom action research, and numeric literacy. The results of the analysis stated that there were changes that occurred in teachers after participating in academic seminar activities. An understanding of the professionalism of elementary school teachers through writing scientific papers, classroom action research and numeracy in learning which was previously ignored makes writing works interesting. Keywords: teacher professionalism, scientific work, classroom action research, numeracy literacy